Marquise Brinvillier : Celebrated Crimes - Dumas, Alexandre, 1802-1870 (Salt Lake City, UT : Project Gutenberg, 2004)
(3z(BThe Marquise de Brinvilliers(3y (Bby Alexandre Dumas is a historical novel likely written in the late 19th century. The narrative centers on the infamous figure of Marie-Madeleine de Brinvilliers, a woman embroiled in scandal and crime during the 17th century, particularly around her relationships and the dark secrets of poison and murder that bind her to her lover, Sainte-Croix. At the start of the tale, readers are introduced to a dramatic scene on the Pont-Neuf where the Chevalier Gaudin de Sainte-Croix is arrested by police during an outing with the veiled Marquise de Brinvilliers. Flashbacks reveal their passionate and illicit love affair, against the backdrop of her tumultuous marriage and the encroaching intrigues of her family. As Sainte-Croix is taken to the Bastille, he encounters Exili, a notorious poison expert, and is gradually drawn into the supernatural allure of vengeance and dark practices. This opening portion vividly sets the stage for a tale of ambition, betrayal, and the escalating descent into criminality that characterizes the lives of both Sainte-Croix and the Marquise. (This is an automatically generated summary.)s
Release date is 2004-09-22
Produced by David Widger
Keywords: Crime